Why does currency denomination in external liabilities of small island developing states matter? Evidence from Fiji. Issue 3 (22nd August 2022) - Jain, Devendra Kumar; Singh, Rup; Kumar, Henali; Kumar, Nikeel; Patel, Arvind
Abstract: The valuation effects on international investment position induced by the exchange rate volatility are not uniform or easily manageable in small and vulnerable economies when compared with larger developing or developed countries. To investigate the underlying dynamics, we developed a foreign currency exposure index over the period 2006–2019. The positive reading of the index suggests that though Fiji has a high net negative international investment position (90% of its GDP), it does not pose any serious risk. To ascertain determinants of Fijiʼs exposure index, we applied fully modified ordinary least square and autoregressive distributed lag bounds test. We have compared both estimates for consistency. Our findings suggest that the underlying determinants of Fijiʼs currency exposure are foreign debt, trade openness and exchange rate. This article bridges the gap in the literature on currency exposure risks in small island developing states and is the first study of its kind for the Pacific region.